Anguilla anguilla ... - Derbal, Farid; Hamdi, Sandra; Rouag-Laouira, Lydia; Chaoui, Lamya; Kara, Mohamed Hichem (Zenodo, 2022)
RESULTS Figure 2 shows the evolution of the digestive vacuity of A. anguilla from Mellah lagoon and Wadi El Kebir, according to sampling seasons and silvering stage. The seasonal maximum and minimum values of the coefficient of digestive vacuity are higher in Mellah lagoon (72.2% and 31.3%) than in Wadi El Kebir (56.1% and 25.8%), with respective annual averages of 53.1% and 42.9%. Statistical analysis showed the existence of seasonal changes in the digestive vacuity in both sites (χ2 ML = 71.014; χ2 WEK = 37.803; P = 0.000). The digestive vacuity in yellow and intermediary eels are less than 50% while those of silver eels is almost 90% in Mellah lagoon and null in Wadi El-Kebir. In these two sites, digestive vacuity is significantly different between the three silvering stages (χ2 ML = 33.309, P = 0.000; χ2 WEK = 7.907, P = 0.019). Tables I and II summarize the composition of the diet of A. anguilla and the classification of taxa ingested in Mellah lagoon and Wadi El Kebir, respectively. Qualitative ... : Published as part of Derbal, Farid, Hamdi, Sandra, Rouag-Laouira, Lydia, Chaoui, Lamya & Kara, Mohamed Hichem, 2022, Diet of the European eel Anguilla anguilla (Linnaeus, 1758) in two transitional waters of Southwestern Mediterranean, pp. 3-11 in Cybium 46 (1) on pages 5-6, DOI: 10.26028/cybium/2022-461-001, http://zenodo.org/record/10836082 ...